Life Cycle Assessment of Construction and Demolition Waste Management in Tehran, Iran - Mohammad Javad Amiri; Mehdi Asadbeigi (Environmental Energy and Economic Research)
The rapid growth of urbanization, along with the extensive construction of infrastructure and real estate projects, has resulted in higher rates of Construction and Demolition Waste (C&D waste). This condition, combined with the lack or inefficiency of municipal programs to manage C&D waste, has exacerbated urban issues related to C&D waste collection, transportation, and disposal. The purpose of the present study is to apply the Life Cycle Assessment methodology to evaluate the environmental performance of the current management of C&D waste and to identify critical aspects and possible improvement actions in Tehran City. Impact 2002+ performs LCA of the base case (19% recycling), two treatment scenarios. These scenarios included the combined use of landfill, sorting and recycling, and the use of C&D waste in varying percentages. The life cycle inventory analysis was carried out using primary data from field studies and secondary data from the Ecoinvent 3.7 database and the literature. The results demonstrate the benefits of C&D waste recycling in terms of avoided impacts of non-renewable energy, global warming, non-carcinogens, and potentially generated respiratory inorganics and organics from landfill. Thus, our results help ensure that decision-making processes are based on environmental and technical aspects and not just economic and political factors and motivate producers to reduce sources and encourage recyclers and concerned organizations to continuously improve the performance of C&D waste management systems across Iran, and also provide data and support for other LCA studies on C&D waste.